A Green-Mediterranean Diet, Supplemented with Mankai Duckweed, Preserves Iron-Homeostasis in Humans and Is Efficient in Reversal of Anemia in Rats. Issue 6 (27th March 2019) - Yaskolka Meir, Anat; Tsaban, Gal; Zelicha, Hila; Rinott, Ehud; Kaplan, Alon; Youngster, Ilan; Rudich, Assaf; Shelef, Ilan; Tirosh, Amir; Brikner, Dov; Pupkin, Efrat; Sarusi, Benjamin; et al.
ABSTRACT: Background: Decreased dietary meat may deplete iron stores, as plant-derived iron bioavailability is typically limited. Objectives: We explored the effect of a low-meat Mediterranean (green-MED) diet, supplemented with Wolffia globosa duckweed (Mankai: rich in protein and iron) as a food source for humans, on iron status. We further examined the iron bioavailability of Mankai in rats. Methods: Two hundred and ninety-four abdominally obese/dyslipidemic [mean age = 51.1 y; body mass index (kg/m 2 ) = 31.3; 88% men] nonanemic participants were randomly assigned to physical activity (PA), PA + MED diet, or PA + green-MED diet. Both isocaloric MED groups consumed 28 g walnuts/d and the low-meat green-MED group further consumed green tea (800 mL/d) and Mankai (100 g green shake/d). In a complementary animal experiment, after 44 d of an iron deficiency anemia–inducing diet, 50 female rats (age = 3 wk; Sprague Dawley strain) were randomly assigned into: iron-deficient diet (vehicle), or vehicle + iso-iron: ferrous gluconate (FG) 14, Mankai 50, and Mankai 80 versions (1.7 mg · kg −1 · d −1 elemental iron), or FG9.5 and Mankai 50-C version (1.15 mg · kg −1 · d −1 elemental iron). The specific primary aim for both studies was changes in iron homeostasis parameters. Results: After 6 mo of intervention, iron status trajectory did not differ between the PA and PA + MED groups. Hemoglobin modestly increased in the PA + green-MED group (0.23 g/dL) compared with PA (−0.1 g/dL; P  < 0.001) and PA + MED (−0.1 g/dL; P  < 0.001). Serum iron and serum transferrin saturation increased in the PA + green-MED group compared with the PA group (8.21 μg/dL compared with −5.23 μg/dL and 2.39% compared with −1.15%, respectively; P  < 0.05 for both comparisons), as did folic acid ( P  = 0.011). In rats, hemoglobin decreased from 15.7 to 9.4 mg/dL after 44 d of diet-induced anemia. After depletion treatment, the vehicle-treated group had a further decrease of 1.3 mg/dL, whereas hemoglobin concentrations in both FG and Mankai iso-iron treatments similarly rebounded (FG14: +10.8 mg/dL, Mankai 50: +6.4 mg/dL, Mankai 80: +7.3 mg/dL; FG9.5: +5.1 mg/dL, Mankai 50-C: +7.1 mg/dL; P  < 0.05 for all vs. the vehicle group). Conclusions: In humans, a green-MED low-meat diet does not impair iron homeostasis. In rats, iron derived from Mankai (a green-plant protein source) is bioavailable and efficient in reversal of anemia. This trial was registered at clinicaltrials.gov as NCT03020186.